Cleaner and sustainable processes for extracting phenolic compounds from bio-waste. (1st November 2020) - Zalazar-García, Daniela; Torres, Erick; Rodriguez-Ortiz, Leandro; Deng, Yimin; Soria, José; Bucalá, Verónica; Rodriguez, Rosa; Mazza, Germán
Abstract: The frequent environment-unfriendly treatments of agro-industrial bio-wastes cause severe pollution through air pollution and through residual effluents and hazardous solid waste. These bio-wastes can contain phenolic compounds, forms of phenolic acids and flavonoids in plants. They are however the most abundant class of many phytochemicals and have been given great interest due to their health advantage and high economic value. An interesting upgrading of these bio-wastes may consist in obtaining a concentrated extract of phenolic compounds using no-toxic solvents, hence protecting the environment and human health. In this work, different alternatives of the extraction process were evaluated using an exergetic analysis. The energy and water consumptions, CO2 emissions, exergetic yield, wasted and destroyed exergy were calculated. It was found that several alternatives for recycle streams were convenient (streams with higher chemical exergy were not discharged into the environment). The energy and water consumption for the best alternative (ethanol-water ratio 1/1 including recycle stream, named E-W 1/1 Rec) were 567 MJ/h and 105 kg/h, respectively and the CO2 emission was 105 kg/h. The calculated exergy destruction indicated that the evaporation and distillation stages may be optimized towards a more sustainable operation. It is not advisable to dry the bio-waste if it will be immediately processed once generated. Graphical abstract: Image 1 Highlights: Eco-friendly alternative for obtaining polyphenols from bio-waste. Energy and water consumptions are evaluated. Alternatives including recycle streams, drying stages and different ethanol-water ratios are considered. CO2 emission, environmental indicators and exergy efficiency are calculated.